DOES DIGITAL GAME ADDICTION AFFECT INTERPERSONAL RELATIONSHIPS IN ADOLESCENTS - POLAT, Filiz; ŞİMŞEK, Didem Coşkun (Göbeklitepe Medical Science Journal, 2021)
This study was conducted to evaluate digital game addiction and interpersonal relationships in adolescents. The sample of this descriptive-cross sectional study consisted of a total of 228 students between the ages of 14 and 17 studying in three public schools. The data in the study were collected online between April and May 2021. The data were collected by using Descriptive Information Form, Digital Game Addiction Scale and Approval Dependence Subscale and Emotional Awareness Subscale of Scale of Dimensions of Interpersonal Relationship. Positive correlation was found between the mean emotional awareness subscale of interpersonal relationship scale and digital game addiction scale scores of adolescents (r=0.196, p=0.003). It was found that adolescents’ emotional awareness increased as their digital game addiction increased and their digital game addiction increased as the time they spent on the internet increased. Adolescents should be made aware of digital game addiction, they should be guided to social environments and the relationships they build in these environments should be supported.